Analysis of the Performance of Elementary School Supervisors in Improving the Quality of Education in West Aceh District - Yulidarna, Yulidarna; Sariakin, Sariakin; Kasmini, Lili (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the performance of elementary school supervisors in improving the quality of education in West Aceh district. This study uses a qualitative research approach. The type of research is descriptive. The sample of this study amounted to 20 respondents, with a snowball sampling technique. Data collection techniques used in this study were interviews, observations. Qualitative data analysis techniques are divided into four parts, namely data collection, data reduction, display and data verification. The results of the study prove that the performance of elementary school supervisors in improving the quality of education in West Aceh Regency is carried out with several actions, namely monitoring, supervision, evaluation, coaching and reporting performance, through these actions there is an increase in the quality of education in West Aceh Regency.